Pembelajaran Drama pada Masa Pandemi Covid-19 - I Gede Nurjaya; I Nyoman Yasa; Ni Made Ermadwicitawati; SAP Sriasih (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Teaching and learning drama in junior high schools is very important in increasing students' appreciation of literature and instilling character values. However, the Covid-19 pandemic has had an adverse impact on the implementation of drama learning in schools. This qualitative research describes teachers' learning tools during the Covid-19 pandemic, the implementation of drama learning, and the obstacles teachers face in implementing drama learning during the Covid-19 pandemic. The subjects of this research were junior high school Indonesian teachers in Singaraja City, Bali. Data was collected through documentation study techniques, interviews, and observation. The results showed that the drama learning tools made by Indonesian language teachers during the Covid-19 pandemic were complete and reflected the 21st-century learning tools. The implementation of drama learning was carried out online by utilizing the Google platform and other online media. The obstacle faced by teachers is the internet network which is often interrupted. The results of this study are very useful, especially as a learning strategy during times of crisis or implementing online language and literature learning.